2010
DOI: 10.1007/s00436-010-1816-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of medicinal plant extracts against blood-sucking parasites

Abstract: The present study was based on assessments of the antiparasitic activities to determine the efficacies of acetone, chloroform, ethyl acetate, hexane, and methanol dried leaf, flower, and seed extracts of Cassia auriculata L., Rhinacanthus nasutus KURZ., Solanum torvum Swartz, Terminalia chebula Retz., and Vitex negundo Linn. were tested against larvae of cattle tick Rhipicephalus (Boophilus) microplus Canestrini, 1887 (Acari: Ixodidae), adult of Haemaphysalis bispinosa Neumann, 1897 (Acarina: Ixodidae), hemato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(21 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…Therefore, the leaf methanol extract of R. communis and leaf chloroform extract of A. malabarica against H. bispinosa and H. maculata used were highly effective and used as an acaricidal and insecticidal activities compounds, respectively. This has been observed earlier by Kamaraj et al (2010) that the leaf methanol of Rhinacanthus nasutus, leaf and seed methanol of Solanum torvum, and seed acetone of Terminalia chebula against the adult of H. bispinosa (LC 50 =333.15,328.98,312.28,and 186.46 ppm;LC 90 =1,056.07,955.39,946.63,and 590.76 ppm), the leaf methanol of Cassia auriculata, the leaf and flower methanol of R. nasutus, the leaf ethyl acetate of S. torvum against the H. maculata (LC 50 =303.36,177.21,204.58,and 211.41 ppm;LC 90 = 939.90,539.39,599.43,and 651.90 ppm). Similarly, Zahir et al(2009) have reported that the parasite mortality was found in the leaf ethyl acetate extract of Achyranthes aspera, leaf methanol extract of A. malabarica, flower methanol extract of G. superba, and leaf methanol extract of R. communis against the larvae of Rhipicephalus microplus (LC 50 =265.33,95.97,153.73,and 181.49 ppm;LC 90 =1,130.18,393.88,1,794.25,and 1,829.94 ppm); leaf acetone and chloroform of A. malabarica, flower acetone Control-nil mortality.…”
Section: Resultssupporting
confidence: 68%
“…Therefore, the leaf methanol extract of R. communis and leaf chloroform extract of A. malabarica against H. bispinosa and H. maculata used were highly effective and used as an acaricidal and insecticidal activities compounds, respectively. This has been observed earlier by Kamaraj et al (2010) that the leaf methanol of Rhinacanthus nasutus, leaf and seed methanol of Solanum torvum, and seed acetone of Terminalia chebula against the adult of H. bispinosa (LC 50 =333.15,328.98,312.28,and 186.46 ppm;LC 90 =1,056.07,955.39,946.63,and 590.76 ppm), the leaf methanol of Cassia auriculata, the leaf and flower methanol of R. nasutus, the leaf ethyl acetate of S. torvum against the H. maculata (LC 50 =303.36,177.21,204.58,and 211.41 ppm;LC 90 = 939.90,539.39,599.43,and 651.90 ppm). Similarly, Zahir et al(2009) have reported that the parasite mortality was found in the leaf ethyl acetate extract of Achyranthes aspera, leaf methanol extract of A. malabarica, flower methanol extract of G. superba, and leaf methanol extract of R. communis against the larvae of Rhipicephalus microplus (LC 50 =265.33,95.97,153.73,and 181.49 ppm;LC 90 =1,130.18,393.88,1,794.25,and 1,829.94 ppm); leaf acetone and chloroform of A. malabarica, flower acetone Control-nil mortality.…”
Section: Resultssupporting
confidence: 68%
“…Aristolochia indica is used in traditional medicine against intestinal worms and is useful in all types of poisonous bites and stings; the crude hexane, ethyl acetate and methanol extracts of A. indica were active for adulticidal, repellent and larvicidal activity against adult and early fourth-instar larvae of Culex gelidus and Culex quinquefasciatus (Kamaraj et al 2010b); the in vitro test of petroleum ether and chloroform extracts of Aristolochia bracteolate extracts caused 100% inhibition of schizont maturation of P. falciparum (Ahmed et al 2010) and the root hexane extract of Holostylis reniformis (Aristolochiaceae) was the most active in vivo against Plasmodium berghei and in vitro against a chloroquine-resistant strain of P. falciparum (de Andrade-Neto et al 2007). Cassia species have been of medical interest due to their good therapeutic value in folk medicine; the acetone, chloroform, ethyl acetate, hexane, methanol and petroleum ether extracts of the leaf and flower of Cassia auriculata are known to be most active against the fourth-instar larvae of Anopheles subpictus and Culex tritaeniorhynchus ).…”
Section: Introductionmentioning
confidence: 99%
“…Kamaraj et al (2010b) reported the adulticidal, repellent and larvicidal activity of the crude hexane, ethyl acetate and methanol extracts of J. procumbens which were tested against adult and early fourth-instar larvae of C. gelidus and C. quinquefasciatus. Catharanthus roseus (Apocynaceae), commonly known as the tropical periwinkle, is a plant of medicinal importance due to its anti-cancer and antitumour activities which are attributed to the presence of the alkaloids vincristine and vinblastine in its leaves.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive work has been done on plant based natural products having acaricidal activities against many species of ticks (Borges et al 2003;Pereira and Famadas 2006;Fernandes and Freitas 2007;Kamaraj et al 2010;de Souza Chagas et al 2012;Juliet et al 2012;Sunil et al 2013) including acaricide resistant species as the natural products can delay the development of resistance due to the presence of a number of active molecules having different mode of action (Wang et al 2007).…”
Section: Introductionmentioning
confidence: 99%